PENINGKATAN SIKAP TOLERANSI MELALUI PENDEKATAN MULTIKULTURAL - THERESIA, NENDEN (PPs UNJ, 2011)
The objective of this research is to know: the learning process to increase multicultural approach kindergarten student of 6 years through multicultural approach based on folktales and change of attitude towards tolerance after the implementation. 12 students of Qurrota Aâyun kindergarten Bandar Lampung are the research subject. This research uses action research method according to Kemmis and Mc Taggart that consist of four steps: plan, action, observation, and reflection. Data collecting techniques uses field notes, interview, documentation, and observation. This research uses descriptive analysis. The result of the research describe that multicultural approach on folktales gives impact for increasing attitude towards tolerance of 6 years old. The result shows increase of 50,5 %.Keywords: increase, multicultural, kindergarten